Opposing influences of global and local stimulus-hand proximity on crosstalk interference in dual tasks. - Ellinghaus, Ruben; Janczyk, Markus; Wirth, Robert; Kunde, Wilfried; Fischer, Rico; Liepelt, Roman (Quarterly Journal of Experimental Psychology, 2023)
In contrast to traditional dualistic views of cognition, visual stimulus processing appears not independent of bodily factors such as hand positioning. For example, reduced crosstalk between two temporally overlapping tasks has been observed when the hands are moved into the attentional window alongside their respective stimuli (i.e., establishing global stimulus-hand proximity). This result indicates that hand-specific attentional processing enhancements support a more serial rather than parallel processing of the two tasks. To further elucidate the nature of these processing modulations and their effect on multitasking performance, the present study consisted of three interrelated crosstalk experiments. Experiment 1 manipulated global stimulus-hand proximity and stimulus-effect proximity orthogonally, with results demonstrating that hand proximity rather than effect proximity drives the crosstalk reduction. Experiment 2 manipulated the physical distance between both hands (i.e., varying local stimulus-hand proximity), with results showing weak evidence of increased crosstalk when both hands are close to each other. Experiment 3 tested opposing influences of global and local stimulus-hand proximity as observed in Experiment 1 and 2 rigorously within one experiment, by employing an orthogonal manipulation of these two proximity measures. Again, we observed slightly increased crosstalk for hands close to each other (replicating Experiment 2); however, in contrast to Experiment 1, the effect of global stimulus-hand proximity on the observed crosstalk was not significant this time. Taken together, the experiments support the notion of hand-specific modulations of perception-action coupling, which can either lead to more or less interference in multitasking, depending on the exact arrangement of hands and stimuli.